The (Neutrophils + Monocyte)/Lymphocyte Ratio Is an Independent Prognostic Factor for Progression-Free Survival in Newly Diagnosed Multiple Myeloma Patients Treated With BCD Regimen - Pang, Yanbin; Shao, Hong; Yang, Ziheng; Fan, Lixia; Liu, Wenwen; Shi, Jianhong; Wang, Yuqing; Han, Ying; Yang, Lin (Frontiers in Oncology, 2020)
Objective: The purpose of this study is to determine the prognostic significance of the (neutrophils+monocytes)/lymphocytes ratio (NMLR) in newly diagnosed MM patients who received BCD regimen therapy in terms of progression-free survival (PFS). Methods: A total of 150 patients who fulfilled the International Myeloma Working Group (IMWG) criteria were enrolled in the study retrospectively. The prognostic value of NMLR was evaluated by 150 patients with MM who were treated with BCD (bortezomib+ cyclophosphamide+ dexamethasone) regimen therapy. NMLR was calculated by the ratio of (neutrophils + monocyte) to lymphocytes. According to receiver operating characteristic curves, the cutoff value was 1.90. The patients were divided into high NMLR group (H-NMLR, NMLR≥1.90) and low NMLR group (L-NMLR, NMLR<1.90). The clinical characteristics, treatment responses and PFS of the two groups were analyzed. Results: The median age of the patients was 61 years. Fifty-five (36.67%) patients showed lower NMLR at initial diagnosis. Although NMLR was unable to discriminate prognosis in ISS stage I/Ⅱ patients, interestingly, the addition of NMLR to the ISS further defined prognosis particularly in stage Ⅲ. Low-NMLR group who achieved early immune reconstruction significantly higher than that of the high-NMLR group(P < 0.001). NMLR value was 1.98 ± 1.02 for the patients who achieved early immune reconstruction, which was 3.26 ± 2.52 for the patients without immune reconstruction(P＜0.05). Compared with the H-NMLR group, the levels of β2-microglobulin, serum creatinine and calcium were lower, and the very good partial response or better (≥VGPR) ratio was higher in L-NMLR group. The L-NMLR group experienced a superior median PFS compared with the H-NMLR group (24.0 vs. 15.5 months; P＜0.001). In addition, several other prognostic factors of PFS were estimated, including the high-risk cytogenetics, β2-microglobulin and the depth of treatment response 3 months after treatment with BCD regimen. Moreover, NMLR was an independent predictor of PFS including non-high risk cytogenetics (0.587; P = 0.031). Conclusion: In patients with newly diagnosed MM undergoing BCD regimen, the NMLR< 1.90 was an independent prognostic factor for PFS as well as early immune reconstruction and lower disease burden.